Aplikasi Mobile untuk Rehabilitasi Pasca Operasi pada Pasien Fraktur Ekstremitas yang Ditangani dengan ORIF: Systematic Review - Sahrudi Sahrudi; Achmad Fauzi Kamal; Masfuri Masfuri; Kasiyah Junus (Universitas Faletehan, 2025)
Extremity fractures are a significant health problem. This study aimed to analyze the effectiveness of mobile applications in post-operative Open Reduction and Internal Fixation (ORIF) education for patients with extremity fractures, focusing on improving functional status and preventing post-operative complications. This systematic review study searched for Articles from the PubMed, Cochrane, ProQuest, EBSCOhost, and ScienceDirect databases. Of the 518 articles found, 69 met the inclusion criteria, and 10 were further analyzed. The results of the review indicated that the use of mobile applications for post-operative ORIF education can improve functional status and prevent complications compared to standard care. Several studies showed that mobile applications can enhance adherence to treatment regimens, reduce complications, and accelerate the healing process. The development and implementation of mobile applications for post-operative ORIF education hold significant potential for improving functional status and preventing the risk of complications in patients. A comprehensive evaluation of application design, intervention effectiveness, patient adherence, user satisfaction, cost-effectiveness analysis, as well as program sustainability and scalability is essential to ensure the long-term success and benefits of this intervention.